Hábitos de consumo de personas entre 20 a 29 años de los medios de comunicación digitales de Riobamba: caso Los Andes, La Prensa, El Espectador y el Diario de Riobamba, enero – diciembre 2020. - Zambrano Pérez, Pedro Fernando (2023)
The main objective is to analyze the consumption habits of young people from 20 to 29 years old, in the acquisition of information in the digital media of Riobamba: Diario Los Andes, La Prensa, El Espectador and Diario de Riobamba. Being quali-quantitative research, it allows to argue and support the results obtained in the development of the same, based on the argumentation of critical specialists, whose knowledge covers the research from the journalistic and communicational point of view. The research is divided into six chapters, which have been developed and explained truthfully through a small sample. There are several reasons why this research work was carried out, among them is the scarce information found about the consumption habits in the young society of Riobamba. A total of 398 surveys were applied for their respective analysis through a questionnaire, which was tabulated to obtain the desired results; the scientific method was used, through the analysis and deepening of various investigations. The quantitative part of this research are the surveys conducted; while the qualitative part falls on certain aspects such as the identification of the challenge of traditional media in the digital environment, the adaptation to the needs of users, the habits of millennials and centennials and interviews with experts. Finally, with the results obtained in the execution of the research, it is proposed to develop an informative manual on the habits of information consumption